Analysis of Screw Press Machine Performance Using the Overall Equipment Effectiveness Method at PT Agro Synergy Nusantara - Irfandi Ambia; Mahmuddin Marbun; Zuhrahmi DE (LPPM Politeknik Aceh Selatan, 2024)
PT Agro Sinergi Nusantara PKS Aceh Seujahtera is a company engaged in the plantation and processing of oil palm fruit, where the production is in the form of crude palm oil (CPO), palm kernel and fiber. This factory has 2 horizontal type sterilizers with a capacity of 40 tons each. One machine that has a vital role in the production process is the screw press. Based on the results of observations and interviews with the company, it was found that the screw press machine was often damaged in the production process, as a result the production process was stopped and production results were not optimal, besides that the company would also experience losses. The purpose of this research is to measure the performance of the Screw Press Machine at PT Agro Sinergi Nusantara by calculating OEE through 3 main factors, namely Availability Ratio, Performance Effeciency Ratio, and Quality Ratio and determining corrective actions that can improve the performance of the Screw Press machine. The results of the performance analysis on the screw press machine obtained an Availability Ratio value of 84.52%, Performance Effeciency Ratio of 86.68%, Quality Ratio of 100%, and OEE of 73.37%. Based on a comparison with the Word Class Ideal Standard, only the Quality Ratio value meets the standard while the Availability Ratio, Performance Effeciency Ratio, and OEE have not met, meaning that the overall performance of the Screw Press Machine has decreased and has not met the Word Class Ideal Standard and it is necessary to improve the performance of the machine. Recommendations for improvements that can be made to improve the performance of the screw press machine again are to carry out routine maintenance on machine components so that damage can be prevented before severe damage occurs and cause longer downtime, conduct training for workers so that they can develop themselves and know more about the machine and the responsibilities that must be carried out, reinforce the implementation of routine and scheduled maintenance (preventive maintenance), and increase supervision during the FFB sorting process.